Children, society, and the aims of education: a source-study and historiographical analysis of two pedagogical essays in the journal “Maorif va oʻqitgʻuchi” (Tashkent, 1925, No. 3) - Yaminxon Muxammedovich Askarxodjayev (Science and Education, 2026)
This article offers a source-critical (manbashunoslik) and historiographical reading of two pedagogical essays published in the third issue (1925) of the Tashkent journal Maorif va oʻqitgʻuchi: a serialised treatise on the aims of education, “Tarbiya gʻoyalari” (“The Aims of Education,” pp. 34-40), and an essay on children’s literature, “Bolalar adabiyoti toʻgʻrisida bir fikr” (“A Thought on Children’s Literature,” pp. 30-33), signed “Olim.” Both texts are written in the reformed Arabic-based Uzbek orthography of the mid-1920s and have not previously been subjected to a dedicated source-critical reading. Combining external and internal source criticism, paleographic observation, lexical analysis of loanwords, and the historical-comparative method, the study reconstructs the texts as material artifacts and traces their intellectual lineages. It argues that the two essays jointly document a decisive moment of transition in Uzbek pedagogical thought at the threshold of the Uzbek SSR. The essay on children’s literature fuses a Jadid concern with moral-aesthetic formation (tarbiya, axloq, zavq) with European and Russian child-developmental psychology and progressive-education aesthetics; the treatise on educational aims grafts the Aristotelian premise that “man is a social animal,” the European tradition of social pedagogy (Sozialpädagogik in the lineage of P. Natorp), and an exact knowledge of classical and medieval educational history (Quintilian’s Institutio Oratoria, the seven liberal arts, the seven knightly accomplishments) onto an emergent Marxist periodisation of social formations. The dense stratum of Russian loanwords (xarakter, egoist, krepostnoy, vassal, ritsar, grajdan) is identified as a philological fingerprint of Russian-mediated transmission, while the essays’ quiet equation of the European “monastery” with the Islamic masjid-madrasa is read as a marker of the convergence of Jadid reformism and Soviet anti-clericalism. The findings establish these texts as significant primary sources for the history of Uzbek pedagogy, of children’s literature, and of the intellectual life of the early Soviet period.